2022
DOI: 10.1111/dmcn.15149
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term neurodevelopmental outcome of neonates born at term with perinatal haemorrhagic stroke: A population‐based study

Abstract: Stroke is 17 times more common in the perinatal period than at any time later in childhood. 1 Although the aetiology and presentation of perinatal ischaemic stroke are well studied, 2 data on perinatal haemorrhagic stroke (PHS) are limited. PHS is defined as a neonate presenting with neurological symptoms during the first 28 days after delivery with a focal collection of blood within the brain parenchyma. 3 It may occur as a primary haemorrhage with or without a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…The authors instead suggested identifying brain lesions based on etiology instead of the imaging pattern to predict neurodevelopmental outcome [41]. On the other hand, in previous studies on larger patient population, we showed that in neonates with arterial ischemic stroke, the main MCA stroke, multiple strokes, the involvement of the corticospinal tract and the presence of infection/inflammation were independent predictors of adverse outcome [34], while in neonates with hemorrhagic stroke, the parietal lobe hemorrhage, the involvement of the thalamus/basal ganglia, hemorrhage affecting multiple lobes and seizures on admission were associated with adverse outcome [42].…”
Section: Discussionmentioning
confidence: 57%
“…The authors instead suggested identifying brain lesions based on etiology instead of the imaging pattern to predict neurodevelopmental outcome [41]. On the other hand, in previous studies on larger patient population, we showed that in neonates with arterial ischemic stroke, the main MCA stroke, multiple strokes, the involvement of the corticospinal tract and the presence of infection/inflammation were independent predictors of adverse outcome [34], while in neonates with hemorrhagic stroke, the parietal lobe hemorrhage, the involvement of the thalamus/basal ganglia, hemorrhage affecting multiple lobes and seizures on admission were associated with adverse outcome [42].…”
Section: Discussionmentioning
confidence: 57%
“…Végül, hemiparesis vagy agyidegbénulás az esetek egyharmadában látható [9]. Perinatalis vérzéses stroke-ban egyes szerzők az encephalopathiát (83%) [3], míg mások a görcsöt [10] írták le vezető tünetként. Nem ritka azonban a hypotonia (42%) vagy a légzészavar sem, mely az első életnapokon jelentkezik [3].…”
Section: Klinikai Tünetekunclassified
“…Vérzéses stroke esetén nem találtunk különbséget a frontalis, temporalis, parietalis és occipitalis lebenyek érintettségének gyakorisága között [10]. Magyarországi populációs szintű vizsgálatainkkal azt találtuk, hogy a parietalis lebeny vérzéses stroke-ja a későbbi cerebralparesis és kognitív károsodás rizikóját, míg a basalis ganglionok és/vagy thalamus érintettsége az epilepszia kialakulásának rizikóját emeli meg [10]. A többszörös vérzéses stroke-nak rossz prognózisa van, hiszen a cerebralparesis, az epilepszia és a ventriculoperitonealis sönt beültetésének rizikóját is megemeli [10].…”
Section: Képalkotó Vizsgálatokunclassified
See 2 more Smart Citations